PENGELOLAAN SAMPAH ORGANIK MELALUI MAGGOT: PERSPEKTIF ETIKA LINGKUNGAN DI RW 08, KEDAUNG - Yanto, Ardi; Fatkhuri Fatkhuri (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Data from the National Waste Management Information System (SIPSN) shows that Indonesia produces around 70 million tons of waste in 2022. The majority of waste generation in Depok City comes from households, especially food waste. If this waste is not managed properly, it will cause environmental pollution. Therefore, managing household waste, especially organic waste through cultivating maggots (Larva Black Soldier Fly) is an effective solution in reducing the amount of waste in the environment. These maggot larvae can eat kitchen waste, leftover vegetables and fruit, market waste. Apart from breaking down waste, maggots also have potential as a source of alternative protein, organic fertilizer and biogas. In a program initiated by UPNVJ students and Kedaung Village in Depok City, organic waste management using maggot larvae is implemented in RW 08. This program involves community participation through education and empowerment, thereby minimizing household organic waste through maggot cultivation.